PENGEMBANGAN INTEGRASI SIDALIH ANTARA PILWALI SURABAYA DAN PILGUB JAWA TIMUR: OPTIMALISASI PELAYANAN PUBLIK KPU KOTA SURABAYA - Fauzi, Agus Machfud (Department of Public Administration, Universitas Negeri Surabaya, 2018)
This study aims to unite the Voter Information System (SIDALIH) based online between the Surabaya Mayor Election (PILWALI) and the East Java Governor Election (PILGUB). Both regional governments have a service program for prospective voters so that voters are facilitated for the use of their voting rights.?PILWALI Surabaya, which in the meantime the implementation of local democracy preceded the East Java provincial government, namely in 2015, while the implementation of East Java PILGUB in 2018. Both of these democratic parties have different voter data. The implementation of PILWALI Surabaya 2015 has?data on voters who are included in the Permanent Voter List (DPT) greater than the 2018 East Java PILGUB voter data on the Permanent Voter List (DPT) they have set. In 2018, there will be three years after 2015, the DPT should have been selected to the regions in a region with more data because there are additional residents every day, but the fact that there is a decrease in the number of voters in PILGUB East Java 2018 compared to PILWALI Kota Surabaya 2015. The author has examined the striking differences in the DPT data of both Election events, and how the solutions to the two elections even though the?regional government is different.